Social Movement Campaigns on EU Policy: In the Corridors and in the Streets - Parks, Louisa (Palgrave Macmillan, 2020)
This book assesses how much influence social movements have on EU policy and the means through which influence is secured. Using wide-ranging case studies of campaigns from GMOs to water rights and Internet freedom, it elucidates the important differences between technical and political campaigns